Slawter - Shan, Darren (New York : Little, Brown, 2006)
While on a horror movie set with his Uncle Dervish, Grubbs Grady realizes that his battle with the evil demon master Lord Loss may be about to resume.
Keywords: Demonology -- Juvenile fiction; Magic -- Juvenile fiction; Motion pictures -- Production and direction -- Juvenile fiction; Demonology -- Fiction; Magic -- Fiction; Motion pictures -- Production and direction -- Fiction; Horror stories; Demonology -- Fiction; Magic -- Fiction; Motion pictures -- Production and direction -- Fiction; Horror fiction; Horror fiction